Step
*
3
of Lemma
fs-in-subtype-subspace
1. K : CRng
2. S : Type
3. T : Type
4. strong-subtype(T;S)
5. T ⊆r S
6. respects-equality(S;T)
7. ∀[a,b:S].  (a = b ∈ T ∈ ℙ)
8. ∀f,y:Point(free-vs(K;S)).  (fs-in-subtype(K;S;T;f) 
⇒ fs-in-subtype(K;S;T;y) 
⇒ fs-in-subtype(K;S;T;f + y))
9. f : Point(free-vs(K;S))
10. a : |K|
11. fs-in-subtype(K;S;T;f)
⊢ fs-in-subtype(K;S;T;a * f)
BY
{ (D -1 THEN RepeatFor 2 (UnfoldTopAb 0) THEN Unhide THEN D 0 THEN ExRepD THEN D 0 With ⌜a * b⌝  THEN Auto) }
1
1. K : CRng
2. S : Type
3. T : Type
4. strong-subtype(T;S)
5. T ⊆r S
6. respects-equality(S;T)
7. ∀[a,b:S].  (a = b ∈ T ∈ ℙ)
8. ∀f,y:Point(free-vs(K;S)).  (fs-in-subtype(K;S;T;f) 
⇒ fs-in-subtype(K;S;T;y) 
⇒ fs-in-subtype(K;S;T;f + y))
9. f : Point(free-vs(K;S))
10. a : |K|
11. b : basic-formal-sum(K;S)
12. f = b ∈ formal-sum(K;S)
13. bfs-predicate(K;S;p.snd(p) ∈ T;b)
⊢ a * f = a * b ∈ formal-sum(K;S)
2
1. K : CRng
2. S : Type
3. T : Type
4. strong-subtype(T;S)
5. T ⊆r S
6. respects-equality(S;T)
7. ∀[a,b:S].  (a = b ∈ T ∈ ℙ)
8. ∀f,y:Point(free-vs(K;S)).  (fs-in-subtype(K;S;T;f) 
⇒ fs-in-subtype(K;S;T;y) 
⇒ fs-in-subtype(K;S;T;f + y))
9. f : Point(free-vs(K;S))
10. a : |K|
11. b : basic-formal-sum(K;S)
12. f = b ∈ formal-sum(K;S)
13. bfs-predicate(K;S;p.snd(p) ∈ T;b)
14. a * f = a * b ∈ formal-sum(K;S)
⊢ bfs-predicate(K;S;p.snd(p) ∈ T;a * b)
Latex:
Latex:
1.  K  :  CRng
2.  S  :  Type
3.  T  :  Type
4.  strong-subtype(T;S)
5.  T  \msubseteq{}r  S
6.  respects-equality(S;T)
7.  \mforall{}[a,b:S].    (a  =  b  \mmember{}  \mBbbP{})
8.  \mforall{}f,y:Point(free-vs(K;S)).
          (fs-in-subtype(K;S;T;f)  {}\mRightarrow{}  fs-in-subtype(K;S;T;y)  {}\mRightarrow{}  fs-in-subtype(K;S;T;f  +  y))
9.  f  :  Point(free-vs(K;S))
10.  a  :  |K|
11.  fs-in-subtype(K;S;T;f)
\mvdash{}  fs-in-subtype(K;S;T;a  *  f)
By
Latex:
(D  -1
  THEN  RepeatFor  2  (UnfoldTopAb  0)
  THEN  Unhide
  THEN  D  0
  THEN  ExRepD
  THEN  D  0  With  \mkleeneopen{}a  *  b\mkleeneclose{} 
  THEN  Auto)
Home
Index